INOVAÇÃO NO ENSINO SUPERIOR: UM ESTUDO SOBRE OS CURSOS DE CIÊNCIAS CONTÁBEIS EM UNIVERSIDADES FEDERAIS NO RIO GRANDE DO SUL. - Costa, Faber Brum da (2021)
This work is directly related to pedagogical innovation in the Accounting Course at Federal Universities of Rio Grande do Sul. It is understood as a renewal in the process of adapting the pedagogical projects of these courses, following the precepts of the resolution (CNE/CES 10/2004 ), in which it deals, in its references, aspects for the formation of the accounting professional, dealing with a current theme and implementing changes in the concept of innovation in the course curriculum. The objective of this research is to analyze how innovation is evidenced in the pedagogical proposals of Accounting Sciences Courses at universities in RS. To meet the general objective, the following specific objectives were established: a) to analyze the Pedagogical Project of the Accounting course of three Federal Universities of RS; b) identify which are the innovative aspects of the proposals for the Undergraduate Courses in Accounting at each of the surveyed universities; c) point out and reflect on the converging aspects of innovation evidenced in the curricular proposals of the Accounting Sciences Courses at Federal Universities of RS. To answer this question, we carried out a qualitative research, with a documentary and exploratory survey of the curricular matrix, amendments and pedagogical projects of the courses, in search of evidence on themes related to innovation. Three undergraduate courses in accounting sciences, offered by three Federal universities in Rio Grande do Sul, were analyzed. To better understand the proposal of these courses, the research was systematized into categories, through which themes with innovative relationships in the curriculum and in the pedagogical projects, considering that the curricula contemplate innovative proposals supported by the respective resolution (CNE/CES 10/2004) and the concepts of innovation, within the context of the research, the concepts of innovation outlined by Masetto were taken as a theoretical framework. describes the process of innovation in higher education, together with the theoretical approach, it can be concluded that there are innovation processes in the aforementioned researched Universities, being pointed out by processes of readjustment of curricula and pedagogical projects.